The Associations of Lipid Profiles With Cardiovascular Diseases and Death in a 10-Year Prospective Cohort Study - Dong, Jiayi; Yang, Song; Zhuang, Qian; Sun, Junxiang; Wei, Pengfei; Zhao, Xianghai; Chen, Yanchun; Chen, Xiaotian; Li, Mengxia; Wei, Lai; Chen, Changying; Fan, Yao; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: Dyslipidemia is one of the modifiable risk factors for cardiovascular diseases (CVD). Identifying subjects with lipid abnormality facilitates preventative interventions. Objectives: To evaluate the eﬀects of lipid indices on the risks of ischemic stroke (IS), coronary heart disease (CHD), CVD, all-cause death, and CVD death. Methods: The cohort study of 4,128 subjects started in May 2009 and followed up to July 2020. Restricted cubic spline (RCS) regression analysis was used to explore the dose-response relationship between lipid indices with outcomes. Cox proportional hazard regression analysis was used to estimate the association with hazard ratio (HR) and 95% confidence interval (CI). Results: RCS analysis showed that there were significant linear associations of TG with IS, non-HDL-C, ApoB, and TC/HDL-C ratio with all-cause death, non-HDL-C and RC with CVD death, and significant nonlinear associations of ApoB with IS and CVD, TC, LDL-C, ApoAⅠ, and TC/HDL-C ratio with CHD, and TC with all-cause death (all P < 0.10). Cox regression analysis revealed that subjects with TC  155 mg/dl (vs 155-184 mg/dl),  185 mg/dl (vs 155-184 mg/dl), and ApoB  0.7 g/l (vs ≥0.7 g/l) had higher risks of CHD (P  0.05), the adjusted HRs (95% CIs) were 1.933 (1.248-2.993), 1.561 (1.077-2.261) and 1.502 (1.010-2.234) respectively. Subjects with ApoAⅠ  2.1 g/l (vs 1.6-2.1 g/l) and TG  80 mg/dl (vs 80-177 mg/dl) had higher risks of CVD and all-cause death (P  0.05), the adjusted HRs (95% CIs) were 1.476 (1.031-2.115) and 1.234 (1.002-1.519) respectively. Conclusions: Lower or higher levels of TC, higher level of ApoAI, and lower level of ApoB were associated with increased risks of CVD, and lower level of TG was associated with increased all-cause death. Maintaining optimal lipid levels would help to prevent CVD and reduce mortality.